Three Women of Liège - Brown Jennifer N. (Brepols (éditions), 2008)
Elizabeth of Spalbeek, Christina Mirabilis, and Marie d'Oignies were three of the famous late twelfth-/early thirteenth-century 'holy women' from the region of Brabant and Liège: their life stories (written in Latin by Philip of Clairvaux, Thomas of Cantimpré, and Jacques of Vitry) were read throughout later medieval Europe, and Margery Kempe modelled her Book, and her life, upon Marie s. The Latin lives of these beguine saints were not well known in England, but they were translated into English in the fifteenth century, and survive in a single manuscript together in Oxford, Bodleian Library, Douce 114. Three Women of Liège is the first critical edition of these Lives, which represent some of the only evidence of English interest in continental female mysticism. This edition includes an introduction that discusses the role of the manuscript in England and three essays that analyze the roles of these beguines in their Low Countries home of Liège along with the English reception of their lives. The edition itself is also extensively annotated and glossed, making it accessible to any scholar of English medieval literature.
Keywords: Languages and Literature; Social Studies; History; Religious Studies